Oral Contraceptive Use, Muscle Sympathetic Nerve Activity, and Systemic Hemodynamics in Young Women. Issue 3 (September 2015) - Harvey, Ronee E.; Hart, Emma C.; Charkoudian, Nisha; Curry, Timothy B.; Carter, Jason R.; Fu, Qi; Minson, Christopher T.; Joyner, Michael J.; Barnes, Jill N.
Abstract : Endogenous female sex hormones influence muscle sympathetic nerve activity (MSNA), a regulator of arterial blood pressure and important factor in hypertension development. Although ≈80% of American women report using hormonal contraceptives sometime during their life, the influence of combined oral contraceptives (OCs) on MSNA and systemic hemodynamics remains equivocal. The goal of this study was to determine whether women taking OCs have altered MSNA and hemodynamics (cardiac output and total peripheral resistance) at rest during the placebo phase of OC use compared with women with natural menstrual cycles during the early follicular phase. We retrospectively analyzed data from studies in which healthy, premenopausal women (aged 18–35 years) participated. We collected MSNA values at rest and hemodynamic measurements in women taking OCs (n=53; 25±4 years) and women with natural menstrual cycles (n=74; 25±4 years). Blood pressure was higher in women taking OCs versus those with natural menstrual cycles (mean arterial pressure, 89±1 versus 85±1 mm Hg, respectively; P =0.01), although MSNA was similar in both groups (MSNA burst incidence, 16±1 versus 18±1 bursts/100 heartbeats, respectively; P =0.19). In a subset of women in which detailed hemodynamic data were available, those taking OCs (n=33) had similar cardiac output (4.9±0.2 versus 4.7±0.2 L/min, respectively; P =0.47) and total peripheral resistance (19.2±0.8 versus 20.0±0.9 U, respectively; P =0.51) as women with natural menstrual cycles (n=22). In conclusion, women taking OCs have higher resting blood pressure and similar MSNA and hemodynamics during the placebo phase of OC use when compared with naturally menstruating women in the early follicular phase.